2021
DOI: 10.1038/s41467-021-23107-x
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-deficiency driven charged out-of-phase boundaries for giant electromechanical response

Abstract: Traditional strategies for improving piezoelectric properties have focused on phase boundary engineering through complex chemical alloying and phase control. Although they have been successfully employed in bulk materials, they have not been effective in thin films due to the severe deterioration in epitaxy, which is critical to film properties. Contending with the opposing effects of alloying and epitaxy in thin films has been a long-standing issue. Herein we demonstrate a new strategy in alkali niobate epita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…[ 84 ] Domains can be visualized using various imaging methods depending on their sizes such as light microscopy, [ 85,86 ] piezoresponse force microscopy (PFM), [ 87–89 ] scanning electron microscopy (SEM), [ 90,91 ] transmission electron microscope (TEM), [ 35,36,92 ] and scanning transmission electron microscopy (STEM) [ 93–95 ] (Figure 5c–h). Advanced imaging techniques such as high‐angle annular dark‐field (HAADF) imaging in aberration‐corrected STEM can reveal quantitative information regarding domains and domain walls even at lattice scale [ 30,41,94,96 ] (Figure 5h).…”
Section: Strategies For Improving Piezoelectric Responsementioning
confidence: 99%
See 3 more Smart Citations
“…[ 84 ] Domains can be visualized using various imaging methods depending on their sizes such as light microscopy, [ 85,86 ] piezoresponse force microscopy (PFM), [ 87–89 ] scanning electron microscopy (SEM), [ 90,91 ] transmission electron microscope (TEM), [ 35,36,92 ] and scanning transmission electron microscopy (STEM) [ 93–95 ] (Figure 5c–h). Advanced imaging techniques such as high‐angle annular dark‐field (HAADF) imaging in aberration‐corrected STEM can reveal quantitative information regarding domains and domain walls even at lattice scale [ 30,41,94,96 ] (Figure 5h).…”
Section: Strategies For Improving Piezoelectric Responsementioning
confidence: 99%
“…During the film growth, 3D nanopillars are formed (Figure 23c–e) with similar crystal structure as the ferroelectric matrix separated by OOP boundaries which display different valence states. [ 41 ] The OOP boundaries surrounding the nanopillars carry two pairs of head‐to‐head and tail‐to‐tail polarizations which appear on the opposite sides of the nanopillar (Figure 23f), showing that the boundaries surrounding the pillar are oppositely charged. Based on phase field simulations, it has been shown that the pairs of oppositely charged OOP boundaries create a strong depolarization field, E dep .…”
Section: Strategies For Improving Piezoelectric Responsementioning
confidence: 99%
See 2 more Smart Citations
“…Piezoelectrics, due to their ability of interconversion between electrical energy and mechanical strain, are widely applied in electro-mechanical devices. Environmental problems make it urgent to develop new lead-free piezoelectric materials with high performance [44,55,[113][114][115][116][117][118][119][120][121][122][123][124]. The lack of basic comprehension of the mechanisms at local level has hindered development.…”
Section: Piezoelectrics: Nano-scale Coexistence Of Phases With Gradual Polarization Rotation For High Piezoelectricitymentioning
confidence: 99%